Evaluation of the Immunogenicity of T and B Cell Epitopes from the S And M Proteins of Sars-Cov-2 Wuhan and Omicron Strains in Balb/C Mice - Kanwal, Khalid * (2024)
The coronavirus disease (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has resulted in numerous infections and deaths. The emergence of SARS-CoV-2 variants of concern (VOCs) resulted in reductions in the protective efficacies of current mRNA and viral-vectored vaccines targeting the spike (S) protein from the SARS-CoV-2 Wuhan strain. A more promising strategy involves targeting highly conserved and immunogenic sequences from SARS-CoV-2 structural proteins to produce immune responses against the Wuhan strain and circulating VOCs. Recombinant protein vaccines could serve as a valuable vaccine development platform based on their high stability, safety, and immunogenicity in clinical development. This research project aimed to develop a recombinant protein vaccine against SARS-CoV-2. Antigens were identified through literature mining and derived from the SARS-CoV-2 S and membrane (M) in the form of six peptides specifying highly conserved B cell and T cell epitopes. The expressed recombinant protein of interest, GST-6Phis, was purified through ammonium sulphate precipitation, gel filtration, immobilized metal affinity chromatography (IMAC), nickel-nitrilotriacetic acid (Ni-NTA) histidine affinity chromatography, and a protein concentrator. Four groups of 5 BALB/c mice each were intramuscularly or intranasally immunized with 10 µg GST-6Phis or with PBS. Cellular and humoral responses were evaluated at 42 days’ post-immunization. Intramuscular administration of GST-6Phis resulted in IFN-γ secreting CD4+ T cells, while intranasal administration produced IFN-γ secreting CD8+ T cells. Robust IgG antibody responses, as represented by absorbance values and mean reciprocal antibody titters, resulted from the intramuscular and intranasal administration of GST-6Phis. Sera obtained from mice immunized both intramuscularly and intranasally with GST-6Phis contained neutralizing antibodies against the SARS-CoV-2 Wuhan strain, while intramuscular administration produced neutralizing antibodies against Omicron. In conclusion, the recombinant protein vaccine demonstrated the promise of utilizing conserved and immunogenic epitopes to produce immune responses against both the SARS-CoV-2 Wuhan and Omicron strains.